Recent developments in spin transfer torque MRAM - Sbiaa, Rachid (2020)
Spin transfer torque (STT) switching‐based magnetic random access memory (MRAM) is gaining significant industrial and academic attention due to its potential application as a non‐volatile memory device in computing devices, smartphones, and so on. STT‐MRAM devices with in‐plane magnetization configuration have been marketed as niche products. Devices with out‐of‐plane magnetization are being considered for embedded memory as the first step. Aggressive goals include replacing dynamic random access memory (DRAM) with STT‐MRAM. This review article introduces the basics of STT‐MRAM and describes the recent progress in overcoming certain challenges such as reduction of power consumption and increase of storage density, which will make it a strong competitor for DRAM.